2018
DOI: 10.31263/voebm.v71i1.2037
|View full text |Cite
|
Sign up to set email alerts
|

Österreichische Repositorien in OpenDOAR und re3data.org: Entwicklung und Status von Infrastrukturen für Green Open Access und Forschungsdaten

Abstract: Mitteilungen der VÖB 71 (2018) Nr. 1: Repositorien in Österreich 71 academic disciplines they represent, the extent of their content, which software is used, whether already existing interfaces (such as OAI) are available and which policies are being followed for the respective repositories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“… Regional studies: Bauer et al . 86 examined Austrian RDRs, Cho 87 Asian RDRs, Milzow et al . 88 Swiss RDRs, and Schöpfel 89 French RDRs.…”
Section: Resultsmentioning
confidence: 99%
“… Regional studies: Bauer et al . 86 examined Austrian RDRs, Cho 87 Asian RDRs, Milzow et al . 88 Swiss RDRs, and Schöpfel 89 French RDRs.…”
Section: Resultsmentioning
confidence: 99%
“…The landscape of the world RDRs is heterogeneous with respect to data curation, access, sharing, transfer, storage and preservation; and the properties of the RDRs are influenced by their disciplinary background (Austin, 2015;Kindling et al, 2017). Even though the number of registered RDRs on the re3data platform grew up over time (Pampel et al, 2013;Bauer and Ferus, 2018), different studies identified non-compliance of the repositories to standards, absence of persistent identifiers (PIDs) and lack of international certification for the repositories (Austin, 2015;Cho, 2019).…”
Section: About Re3datamentioning
confidence: 99%
“…befanden sich zum Zeitpunkt des Projektabschlusses in Planung oder Umsetzung. 10 Bis zum Projektbeginn 2014 war das Thema Forschungsdatenmanagement an den meisten österreichischen Universitäten nicht oder nur kaum präsent. Deshalb wurden in Teilprojekt B wichtige Maßnahmen auf diesem Gebiet gesetzt.…”
Section: E-infrastructures Austria (2014-2016)unclassified